2017
DOI: 10.1016/j.pmrj.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neck Strength in Healthy Young Adults

Abstract: Background The role of cervical muscle (neck) strength in traumatic brain and spine injury and chronic neck pain disorders is an area of active research. Characterization of the normal ranges of neck strength in healthy young adults is essential to designing future investigations of how strength may act as a modifier for risk and progression in head and neck disorders. Objective To develop a normative reference database of neck strength in a healthy young adult population; and to evaluate the relationship of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
27
2
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(40 citation statements)
references
References 23 publications
7
27
2
4
Order By: Relevance
“…Several studies measured heading acceleration in men and women under controlled conditions and found greater acceleration in response to a similar force applied to women, which was attributed to anatomic differences between the sexes (43)(44)(45). Sex-based divergence of neck strength and anthropometrics (46) may have also played a role in our findings, but other factors such as genetics and hormonal influences may have contributed as well. Future studies examining each of these possibilities, and others, are necessary to uncover the mechanistic basis for the sex differences.…”
Section: Discussionmentioning
confidence: 49%
“…Several studies measured heading acceleration in men and women under controlled conditions and found greater acceleration in response to a similar force applied to women, which was attributed to anatomic differences between the sexes (43)(44)(45). Sex-based divergence of neck strength and anthropometrics (46) may have also played a role in our findings, but other factors such as genetics and hormonal influences may have contributed as well. Future studies examining each of these possibilities, and others, are necessary to uncover the mechanistic basis for the sex differences.…”
Section: Discussionmentioning
confidence: 49%
“…26 Various mechanisms have been postulated as to why men and women have different outcomes following concussion and subconcussive injury, such as force of injury, number of injuries, skull and brain shape, neck strength, and hormonal influences. 27,28 Further investigation, including in animal models, will be necessary to isolate individual aspects of injury and recovery to develop new modes and methods for treatment.…”
Section: Introductionmentioning
confidence: 99%
“…17 Therefore, our findings support the need for increased consideration of comorbid neck injuries to allow for early intervention, particularly for females, who have been found to be most at risk for persistent symptoms. 10,11 Most importantly, the results of this study suggest that the biological differences between males and females, 19,20 which determine the risk of comorbid neck injury, are age-dependent. This study showed a clear interaction between age and sex and, therefore, it is crucial to consider linear and nonlinear sex and age interactions across the life span of patients in future studies on concussions.…”
Section: Discussionmentioning
confidence: 71%
“…, thoracic and lumbosacral) of the spine. 18 Evidence also supports that females have weaker and anatomically distinct necks than males, 19,20 which suggests that the relationship between neck injuries and concussions may be sex-dependent and that biological differences between males and females may be responsible for the observed increased vulnerability among females to sustain whiplash in motor vehicle collisions (MVC), 21,22 poorer prognosis following injury, 23,24 and increased risk of concussion. 25…”
Section: Introductionmentioning
confidence: 98%